Tracing the origins and evolution of yoga darshana: A critical historical analysis - Dave Bansariben Chhellashankar; Anil Kashyap (The Scientific Temper, 2024)
One of India's six classical philosophical traditions, Yoga Darshana, has its origins traced through this article's analytical and empirical research. From its inception in ancient times to its modern interpretations, this inquiry delves into the origins, evolution, and fundamental concepts of Yoga Darshana. Also included in the study is the origins of Yoga Darshana. The study's overarching goal is to fill gaps in our understanding of Yoga Darshana's place in Indian philosophy. To do this, we will look at important texts, have philosophical conversations about them, and consider how religious and cultural factors play a role. The study also delves into the ways in which yoga's fundamental principles have evolved and been reinterpreted throughout the years and how these changes have impacted traditional spiritual practices as well as contemporary health movements. The study aspires to contribute to the continuing discussion on the relevance and usefulness of yoga in both contemporary and traditional settings through its critical historical research.